Pengaruh Oil Sludge Pertamina Surabaya Terhadap Kuat Tekan Keramik Tradisional - Adi Ilcham (Eksergi)
Oil sludge is the solidifying oils that lying on the open space around the fuel storage tank. Heaps of the waste continues to increase could lead to environmental pollution due to the waste containing heavy metal. This research aims to study the effect of oil sludge on the compressive strength of traditional ceramics within range of sintering temperature (600- 1000 0 C), sintering time (1-3 hours), and raw material compositions. The experiment begins by mixing the ceramic raw materials. Material was mixed with water and milled using Mortar Hand (milling). A cermic mold was used to get ceramic specimens. The mold dimension is length of 8 cm, 4 cm wide, and 2 cm high. The specimens were sintered in a furnace at different temperatures and holding time. Finally, the ceramics were observed its compressive strength. The results showed that the waste oil sludge can be involved in the manufacture of traditional ceramics. In the view of the compressive strength, the best conditions for fabricating traditional ceramics are oil sludge of 16.67% w., sintering temperature of 800 0  C, and sintering time of 2.5 hours.